Comparative Analyses Between Vulnerability Biomarkers of Aging and Health Biomarkers in Middle-Aged and Older Female Adults - Knoblauch, Klara Karin Brigitte [UNESP]; Losnack, Luana Froes [UNESP]; Zacarias, Gustavo Castillo [UNESP]; Satyro, Gabriel Gasparini [UNESP]; Villar, Rodrigo; Zago, Anderson Saranz [UNESP] (MDPI, 2025)
Biological aging is normally associated with greater physiological changes which predispose individuals to adverse outcomes. In this way, the evaluation of vulnerability biomarkers and their relationships with other health biomarkers could contribute to the promotion of interventions and the improvement of older adults' quality of life. Thereby, this study aimed to compare vulnerability biomarkers (Growth Differentiation Factor 15 (GDF-15), General Functional Fitness Index (GFFI), and frailty phenotype) and their influence on health markers (blood biochemistry, body composition, and hemodynamic variables) in middle-aged and older female adults. Methods: A cross-sectional observational study was conducted with community-dwelling females aged 54-84 with at least 6 months of experience with physical training. The participants were categorized based on functional fitness, frailty phenotype, and GDF-15 quartiles. The General Functional Fitness Index (GFFI) was assessed using the AAHPERD test battery, while frailty phenotype was determined using Fried's criteria. GDF-15 levels were measured through ELISA. Results: A higher training status (TS) showed better functional fitness and favorable biochemical profiles, including lower total cholesterol (p = 0.006, η2p = 0.253), LDL cholesterol (p = 0.001, η2p = 0.346), triglycerides (p = 0.048, η2p = 0.195), and systolic blood pressure (p = 0.001, η2p = 0.333). Individuals classified as robust (non-frail) had better physical performance and lower total cholesterol (p = 0.002, η2p = 0.306) and LDL cholesterol (p = 0.014, η2p = 0.216) compared to those classified as frail and pre-frail. The GDF-15 quartile did not present differences in health markers between groups. Conclusions: These findings suggest that GFFI may be considered a health biomarker for middle-aged and female older adults while highlighting the need for further research on the role of biomarkers of vulnerability and healthy aging.